Factors Affecting Post-Partum Amenorrhea in Nepalese Women - Shrestha, Ira; Bhandary, Shital (Journal of General Practice and Emergency Medicine of Nepal, 2014)
Introduction: Postpartum Amenorrhea (PPA) is important method of birth control and birth spacing especially in developing countries. Following a live birth, a woman generally experiences a 6-week period of amenorrhea related to the hormonal concomitants of pregnancy but not much work has been done in Nepal regarding the effects of various demographic factors and socioeconomic statuses of women on their postpartum amenorrhea.Methods: This study was based on the 2011 Nepal Demographic and Health Survey (NDHS) datasets. The duration of PPA was the response variable whereas key demographic and socio-economic variables of women and her children were explanatory variables. Since PPA period was not defined for some of women as they were still going through the PPA at the time of the survey, their data were censored. Therefore, survival analysis techniques: Life Tables and Semi-Parametric Hazard (Cox) Models were used.Results: All the demographic and socio-economic variables except the sex of child had statistically different median PPA durations. The bivariate cox models also revealed similar result in terms of relative risk associated with the reference categories. However, multivariate cox model revealed breast feeding, parity, birth interval, survival of the child, education of the mother and wealth quintile of the mother influenced the PPA after controlling the effect of other variables.Conclusions: This study revealed that longer the duration of breastfeeding, greater the delay in the return of menstrual cycle. Survival of child was the most important indicator for PPA among Nepalese women. The gender of the child and place of residence did not make any difference with respect to PPA. Mothers with birth interval of 3-4 years had lesser risk of return of monthly cycle.